Timber use practices in Malaysia’s construction industry: single-family residential building sector - Mohamed, Shukri; Abdullah, R. (Universiti Putra Malaysia Press, 2014)
The importance of domestic timber market in Malaysia is recognised with the launch of the National Timber Industry Plan in 2009, which calls for promoting and encouraging the use of timber products by the local construction industry. A study was conducted to provide information on the current use of timber products in the single-family residential building sector as it is one of the major development projects undertaken by the construction industry. In specific, the study aimed to identify the types and to estimate the amount of timber products used in the construction and those installed in the completed single-family residential building units. Data for the study were collected using a self-administered, openended questionnaire sent to constructions firms in Selangor and the Federal territory of Kula Lumpur advertising the sale of their residential building units in the local newspapers and the internet during the survey period. The respondents of the study were project managers or quantity surveyors who were involved directly in the supervision and monitoring of the residential projects constructed by the construction firms. The amount of sawn timber and plywood used for the construction of the residential units ranges from 0.05 to 0.07 cu. m/sq. m. and 0.01 to 0.07 cu. m./sq. m., respectively. The most common timber products installed in the completed residential units are wooden/timber doors. Other traditional timber-based products are still being used but they are continually replaced by other building materials such as aluminium, steel and glass. Efforts to promote timber products to the single-family residential building sector should target on their uses in the completed residential building units.